Academic Words in the English Research Article Abstracts: the Coverage and Frequency - Fransiskus Jemadi; Fatma Wati; Priska Filomena Iku (Universitas Islam Negeri Walisongo Semarang, 2019)
The present study aimed at exploring the abstracts of research articles written by non-native English researchers to uncover the specific characteristics of academic vocabulary employed in the English research articles abstracts.It focuses on frequency and coverage distribution of the words from the Academic Word List (Coxhead, 2000) in the abstracts of research articles. The source of data for this corpus study was gathered from 97 abstracts written by the EFL researchers and published by the Journal Pendidikan dan Kebudayaan Missio at STKIP St. Paulus Ruteng from 2015 until 2018. The results of this study revealed that the coverage of K1, the first most frequent 1000 English words, is the most dominant lexical items applied by the researchers. It covered 71.33% of the texts. The representation of lexical items that belong to K2, the second most frequent 1000 English words, covered 5.44% of all the words used by the writers in their abstracts. Moreover, the presence of Academic Word List, which refers to a list of 570 word families that are commonly found in academic texts and Off-list, which refers to the words that do not belong to K1 or K2 because it is related to certain field, has slight difference over all of the texts where the former covers 11.95% and the later covers 11.26%. As far as the findings of the present study are concerned, the room for some improvements on academic words applied in the abstracts need to pay attention.